Chemistry - The Savior of Mankind - UiTM, Fakulti Sains Gunaan (Faculty of Applied Sciences, 2021)
ChM. Dr. Shahrul Nizam Ahmad was invited as a guest speaker in virtual event "Chemistry-The Savior of Mankind" on 6 April 2021. The event was part of "Minggu Sains Negara" programme, which was organised by the Ministry of Science, Technology and Innovation (MOSTI), Malaysia.